Theoretical study to determine the proper injection system for upgrading fuel system of diesel engine om357 to common rail system - Pourdarbani, Razieh; Aminfar, Ramin (International Journal of Engineering and Technology, 2018)
In this research, we tried to investigate all the fuel injection systems of diesel engines in order to select the most suitable fuel injection system for the OM357 diesel engine to achieve the highest efficiency, maximize output torque and reduce emissions and even reduce fuel consumption. The prevailing strategy for this study was to investigate the effect of injection pressure changes, injection timing and multi-stage injection. By comparing the engines equipped with common rail injection system, the proposed injector for engine OM357 is solenoid, due to the cost of this type of injector, MAP and controller (ECU). It is clear that this will not be possible only with the optimization of the injection system, and so other systems that influence engine performance such as the engine's respiratory system and combustion chamber shape, etc. should also be optimized.
Keywords: Diesel Engine; Common Rail; NOX; Soot.